PENGARUH BUDAYA KERJA TERHADAP EFEKTIVITAS PELAYANAN PUBLIK KANTOR DESA TIMORENG PANUA KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Cakra Cakra (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Abstract The purpose of this research is to determinate the effect of work culture on the effectiness of public service in the office village of Timoreng Panua, Panca Rijang district, Sidenreng Rappang Regency. The populations of this research is the whole of Family card as much as 547 of 2 hamlets at Timoreng Panua village. The Collecting of Samples using Random Sampling technique and Yount Formula with 10% Standar error, resulting in a sample as much as 55 55 respondents.The data collecting technique of this research is observation, questionnaire, interview and library research. The data analysis of the research used the frecuency distribution tables and simple linaer regresion with SPSS (Statistical Product and Service Solution) 16.0 program for windows.The results showed that the work culture of the effectiveness of public services in the office village ofTimorengPanua,PancaRijang District, SidenrengRappangRegency had a significant influence from the results of calculations in the ANOVA table, t count> t Table or 8.262> 2.672 with a significance level of 0,000 <0, 05, then the decision is Ho “refused” and Ha “accepted”, meaning that work culture (X) has a significant influential on the effectiveness of public service (Y). While the model summary table shows that the influence of work culture (X) on the effectiveness of public service (Y) is 0.563 or 56.3% the category